Penguatan Literasi Politik bagi Generasi Z : (Kajian Sebelum Masa Pemilihan Umum 2024) - Tiyas Nur Haryani; Muhammad Ikhsanul Amin; Arina Mardhiyana Husna; Septiani Maya Lestari (Indonesian Journal Publisher, 2024)
Political dynamics in society has always been an interesting subject in public discussion. Political dynamics occur every day in social life in society. The development of life today is mostly supported by Information and Communication Technology devices as well as the openness of the public making public dynamics occur in the real world as well as in cyberspace. Society must be armed with adequate political literacy for public decision making. Currently, the structure of society has a wider variety of generations, one of which is the postmillennial generation or generation Z. Generation Z Indonesia has participated in the political world. This article seeks to describe collaborative governance efforts in strengthening political literacy for the postmillennial generation. The article was compiled from the results of a literature review study which was finally able to be presented in a narrative. The literature reviews used come from national journals on millennial generation, politics, general elections, generation Z and political literacy published in the period 2018-2020. The results of the literature review show that the political literacy of the postmillennial generation is mostly assisted by social media. Thus, collaborative governance in the superstructure sector and political infrastructure needs to be supported by Information and Communication Technology.